Serbia : Overview of Tobacco Use, Tobacco Control Legislation and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
Serbia has rather high prevalence of smoking. According to the National Health Surveys, the prevalence of daily smoking among men in 2013 was 33 percent which was lower than in 2000 (41 percent), while among women it was almost as high as in 2000 (26 percent). Cigarette smoking among adolescents aged 13-15 years old decreased in 2013-2017; however, the use of electronic cigarettes and waterpipe is growing among young people. To overcome the tobacco epidemic, Serbia became a Party to the WHO Framework Convention on Tobacco Control on May 9, 2006, and implemented some tobacco control policies. Tobacco taxation policy in Serbia in 2009–2013 was very successful from a public health perspective as it reduced tobacco consumption, in line with the FCTC obligations. Estimated tobacco consumption in the country declined by 33 percent in four years. The outflow of cigarettes taxed in Serbia to other countries also declined, while the volume of cigarettes, which were smoked but not taxed in Serbia, did not change much after the tax increases. This taxation policy also increased the tobacco excise revenue from 39 billion RSD in 2008 to 84 billion RSD in 2013 (by 44 percent in real terms). However, the tobacco industry managed to modify the impact of the tobacco taxes. In 2012-early 2014, it vastly increased its (net-of-tax) part of cigarette price, and this reinforced the taxation impact on tobacco sales as the final retail price increased more than expected. As the growth of the industry profit margins was disproportionately soaring, the industry increased its profits despite the decline of tobacco sales. The main factor behind the cigarette sales reduction in 2012-2014 was the industry pricing tactics, while the excise rate increases were rather moderate. The combined effect of government taxes and industry prices substantially reduced cigarette affordability, and the resulting sales decline exceeded the excise burden growth; so, the government excise revenue decreased. In late 2014, the tobacco industry decreased prices for some brands, and it also contributed to the excise revenue decline in 2014, as ad valorem part of cigarette excise was rather high in Serbia.